ANALISIS POTRET KEHIDUPAN SOSIAL EKONOMI PEDAGANG KAKI LIMA STUDI FENOMENOLOGI DI PASAR SUKARAMAI MEDAN - Syariah Fidela; Muhammad Arif; Neila Susanti (Studia Economica : Jurnal Ekonomi Islam, 2021)
This study aims to determine and analyze the picture of the socio-economic life of street vendors in the Sukaramai market in Medan and what developments and obstacles they face. This study uses a qualitative method with a phenomenological approach. The research location is in Sukaramai Market on Jalan A.R Hakim Medan. The informant retrieval technique used is accidental sampling or done randomly or anyone who happens to meet and is considered suitable by the researcher. Data collection techniques used were interviews, observation, and documentation. The data analysis technique used is qualitative data analysis. The results of the research are portraits of the socioeconomic life of the street vendors in the Sukaramai market to obtain sufficient income to fulfill their daily lives. Obstacles faced by street vendors such as raids by Satpol Pp to control street vendors, extortion (illegal levies) by thugs on the grounds of cleanliness and security fees, as well as weather factors such as rain which often overwhelms street vendors because stalls are open in the area.